HUBUNGAN SHIFT KERJA DENGAN KELELAHAN KERJA PADA PERAWAT DI INSTALASI RAWAT INAP DI RS HERNA MEDAN TAHUN 2018 - Nuraini Nuraini (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2019)
Abstract The hospital is a health care facility operates 24 hours. The Responsibilities and workload of nurses to note with the division of labor, such as morning shift, noon shift, and night shift. The division of this shift can give negative impact which one is fatigue. relationships shift work with fatigue on nurses inpatient in RS Herna..The research design is descriptive analytic with a cross sectional approach. The population in this study were all the nurses the inpatientusing a simple random sampling technique as many as 57nurses. Data analysis used statistical test using chi-square. there is a level of fatigue in the category of less tired as many as 12 people (63.2%), tired as many as 7 people (36.8%). And in the noon shift nurse there was a level of fatigue in the category of tiredness as many as 12 people (63.2%), tired as much as 6 people (31.6%) and very tired as much as 1 person (5.3%). At night shift nurses there is a level of fatigue in the category of tiredness as many as 3 people (15.8%), tired as many as 14 people (73.7%) and very tired as much as 2 people (10.5%). From the results in this research obtained a significant value of p = 0.016 or p <0.05. there is a work shift relationship with work fatigue in nurses in inpatient installations at Imelda General Hospital Medan Indonesian Workers. Keywords: Work shift, fatigue and nurse